PERAN DEMONSTRATION SITE STATION TERHADAP PENURUNAN KONSENTRASI AIR LIMBAH RUMAH TANGGA DI SEKITAR SUNGAI CILIWUNG - Melania Hanny Aryantie; Sri Unon Purwati; Alfonsus H Harianja; Muhamad Yusup Hidayat (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2018)
This paper presents the correlation between socio-economic characteristics of the community around Ciliwung river basin with effort to reduce the concentration of household wastewater after treatment by using demonstration site station (DSS). Effects of socio-economic characteristics of the community which are categorized as internal and external factors that encompassed their decision in DSS application was tested by using logistic regression analysis. The results showed that the decision DSS adoption was affected by intrinsic factors such as the mothers’ role on every family and knowledge of the benefits of 3R (reduce, reuse, recycle) in waste management, as well as external factors such as key person leadership regarding household liquid waste management and availability of domestic waste processing installation. Moreover, water quality test after DSS treatment showed that declining concentration of tested parameters were among others: total phosphate (T-P), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solid (TSS), potential of hydrogen (pH), and oil and fat. Oil and fat parameter can be controlled through waste sorting, in DSS, while methylene blue active substances (MBAS) had no effect.